Aksesibilitas Layanan Kesehatan Modern dan Tradisional di Masyarakat Pantai Putra Serdang Pantai Labu Deli Serdang - Astuti, Aprillia Dwi; Ramadhan, Muhammad Rizky; Nafisah, Nailah; Nurjanah, Ana; Utami, Risna; Wasiyem, Wasiyem (CV. Rayyan Dwi Bharata, 2025)
People's quality of life is greatly influenced by the accessibility of health services, especially in marginalized areas such as coastal communities. This study investigates the accessibility of modern and traditional health services in Pantai Labu, Deli Serdang. methods used in this study include literature study and in-depth interviews with ten family members in the area. The results showed that cultural, social, and economic factors are very important when choosing the type of health service. In addition, geographical and economic issues affect how easily people gain access to sufficient health facilities. This research is expected to have a positive impact on the health policy-making process and improve the ability of coastal communities to obtain health services.